2014
DOI: 10.1007/s11596-014-1267-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of MUC15 overexpression with clinicopathological features and prognosis of glioma

Abstract: The abnormal expression of MUC15, a novel cell membrane-associated mucin, has been reported to predict poor survival in several cancers. The aim of the present study was to examine the expression of MUC15 in glioma and its correlation with clinicopathological features, including the survival of patients with glioma. The mRNA expression level of MUC15 was determined by RT-PCR, quantitative RT-PCR (RT-qPCR) and Western blotting in seven normal brain tissues and seven glioma tissues, respectively. The protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Furthermore, KIRC and KIRP both show a dramatic decrease in MUC15 mRNA. MUC15 is an underexplored transmembrane glycoprotein, which has been shown to have various possible roles in cancers [ 36 38 ]. In hepatocellular carcinomas, decreased MUC15 expression was seen and associated with more aggressive phenotypes and shorter survival [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, KIRC and KIRP both show a dramatic decrease in MUC15 mRNA. MUC15 is an underexplored transmembrane glycoprotein, which has been shown to have various possible roles in cancers [ 36 38 ]. In hepatocellular carcinomas, decreased MUC15 expression was seen and associated with more aggressive phenotypes and shorter survival [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinomas, decreased MUC15 expression was seen and associated with more aggressive phenotypes and shorter survival [ 37 ]. However, a reverse trend is seen in glioma, where increased MUC15 correlates positively with progression and stage and serves as an independent factor for prognosis [ 38 ]. MUC15 also has signaling interactions with key growth-modulating signaling pathways such as the epidermal growth factor receptor and phosphoinositide 3-kinase [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who died of diseases not directly related to their gliomas or due to unexpected events were excluded from this study. Several clinicopathological features, such as WHO grade, Karnofsky performance status (KPS) score, and tumor size, have been considered as important prognostic factors for gliomas [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, MUC15 is overexpressed in colon cancer cell lines, activates the p-ERK pathway, and promotes metastasis and invasion [ 17 ]. Subsequently, Yang [ 32 ] showed the MUC15 overexpression was correlated with cancer progression and can be used as a marker for poor prognosis in glioma patients. In thyroid cancer, Choi [ 18 ] showed that MUC15 has a vital function in sphere formation of cancer cells and activates ERK by FAK and GPCR/cAMP pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we proved that MUC15 activated the ERK-MAPK pathway in PC cells by western blot. The PI3K/AKT signaling pathway also promotes the invasion and metastasis of pancreatic cancer [ 32 , 39 ]. Activation of this pathway leads to cell progression, cellular apoptosis, protein synthesis, and genomic instability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%